Contemporary issues in curriculum - Ornstein, Allan C.; Pajak, Edward 1947-; Ornstein, Stacey B. (Boston, Massachusetts Pearson, 2011)
"Featuring 25% new content, the fifth edition of Contemporary Issues in Curriculum addresses issues in implementation, planning, and evaluation of curriculum at all levels of learning. Divided into six parts?Philosophy, Teaching, Learning, Instruction, Supervision, and Policy? the new edition of this balanced yet eclectic text features ten new chapters written by notable authors including Larry Cuban, Howard Gardner, Andrew Hargreaves, Linda Darling-Hammond, and Stanley Pogrow. With each new chapter, readers are asked to consider a new author?s viewpoint, thought process, and conclusions about significant and current curriculum issues, from traditional and commonly accepted beliefs to more controversial and contemporary ideas. Through a variety of learning aids and discussion questions, readers are encouraged to analyze and debate these issues, to formulate their own opinions, and begin to shape their own original ideas about the future direction of curriculum."--Back cover.
Curriculum and philosophy -- Curriculum and teaching -- Curriculum and learning -- Curriculum and instruction -- Curriculum and supervision -- Curriculum and policy.
Keywords: Education -- Curricula -- United States; Curriculum planning -- United States